Kloning di mata moral agama: Kajian kritis atas hokum islam - Syamsun Ni’am (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Cloning is a new phenomenon. As a new phenomenon, it always causes controversy. The controversy does not only occur amang moralists (either islam, jewish, Christianity, or other religion in the world). For scientists, the success of clonig is the achievement of scientific development. While for moralists and religionists and religionists, the success of cloning is a dangerous phenomenon for people in the future thus, moral principles, humanity, honesty, and course, religious law and social ethics must constantly bicom basic consideration in responding cloning phenomenon, in order not to neglect the god’s will.